HUBUNGAN KEKERABATAN Nepenthes HIBRID HASIL PERSILANGAN ALAMI ANTARA Nepenthes mirabillis (Lour.) Druce DAN Nepenthes reinwardtiana Miq BERDASARKAN KARAKTER MORFOLOGI - Dina Oktaviani Azra; Siti Ifadatin; Irwan Lovadi; Rafdinal Rafdinal (Floribunda, 2023)
Nepenthes is a carnivorous plant that can cross-pollinate the same or different species so that it can produce hybrid Nepenthes. An analysis of the relationship between Nepenthes species and their hybrids can be carried out by observing the morphological characters. The purpose of this study was to determine the morphological characteristics and the relationship between Nepenthes hybrids and their parents. This study used Nepenthes hybrid resulting from a cross between N. mirabillis and N. reinwardtiana which were found in Entikong District, Sanggau Regency. The relationships were analyzed using the NTSys program with the UPGMA method. Nepenthes reinwardtiana does not have variations in pitcher color or shape. Nepenthes mirabillis and N. mirabillis X N. reinwardtiana had variations in pitcher color and shape. Nepenthes hybrid has a characters inherited from both parents. Nepenthes reinwardtiana, N. mirabillis, and N. mirabillis X N. reinwardtiana had a similarity level of 0.46 and were divided into three clusters. The relationship between N. mirabillis and N. mirabillis X N. reinwardtiana has the greatest similarity coefficient value of 0.77, while N. reinwardtiana and N. mirabillis X N. reinwardtiana have a similarity coefficient value of 0.64. Morphological characters show clear differences in the pitcher. The relationships of Nepenthes hybrid is closer to N. mirabillis.